KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR RODA DUA DI SAMSAT KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Tefa, Melani Rintan; Adam, Cataryn V.; Seran, Delila A. Nahak (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to analyze the compliance of two-wheeled motor vehicle taxpayers at the Samsat (Service Unit) of Kupang City, East Nusa Tenggara Province. Taxes are a major source of state revenue and play a vital role in financing development and public welfare. However, public compliance in paying motor vehicle taxes in Kupang City remains low, with many unpaid tax arrears. The theory used in this study is the OECD (Organization for Economic Cooperation and Development) compliance theory as cited in Pohan (2017:160). The aspects measured in this compliance theory are registration, reporting, and payment. This study used a qualitative approach with descriptive methods. The results show that taxpayer compliance in registering, reporting, and paying motor vehicle taxes is still suboptimal. The vehicle registration process is carried out according to procedure, but public awareness of registering vehicles and fulfilling their tax obligations remains low. Monthly and annual reporting is carried out well by the Samsat, however, there are obstacles in reporting caused by taxpayer non-compliance. Tax payments are also inadequate because some taxpayers still do not pay their taxes on time and have tax fines, resulting in arrears. Based on these issues, it is recommended that the Samsat (Vehicle Tax Office) conduct outreach on the importance of tax compliance, expand mobile Samsat services, and conduct raids to regulate motor vehicle registrations on the road in collaboration with the Kupang City Traffic Police. These efforts are expected to increase taxpayer awareness and compliance, thereby supporting increased local revenue and development in Kupang City.